The morbidity and the spectrum of applied drugs in shelter cats in the Czech Republic - Vojtkovská, Veronika; Kaluža, Michal; Voslářová, Eva; Večerek, Vladimír; Tomečková, Lenka (Frontiers in Veterinary Science, 2022)
Maintaining appropriate living conditions and good health of the animals should be one of the main priorities of cat shelters. The aim of this study was to assess the morbidity of shelter cats on the basis of analysis of the shelter health records in terms of the nature and quantity of medicaments and other supportive products administered in two no-kill shelters in the Czech Republic. The subject of the study were the health records of 1884 cats, which were admitted to the selected shelters from 1.1.2013 to 31.12.2021 and their stay in the shelter was terminated in the monitored period. More than half of all cats whose records were analyzed had at least one health record made during their stay in the shelter. The overall length of stay of cats in the shelter (regardless of the outcome) in which one or more health records were found was significantly longer compared to the length of stay of cats without any health records. The highest number of health records was found in kittens less than 6 months old. Antibiotics, antiparasitics and complementary/protective substances were the most used among all administered drugs. Broad-spectrum antibiotics have been administered to cats most often. In terms of classification of antibiotics according to the active substance, the most used antibiotics were penicillins, tetracyclines and fluoroquinolones. Antibiotics were mostly used to treat diseases related to the upper and lower respiratory tract and their symptoms and gastrointestinal problems. The findings of the study contribute to understanding health problems and approaches to treating the shelter cats.